H∞ containment of networked MASs with disturbances, position, and velocity constraints. Issue 2 (6th November 2022) - Chen, Jie; Wang, Yalin; Luo, Danni; Hou, Hailiang; Gui, Weihua
Abstract: The objective is to achieve the constrained containment of discrete‐time multiagent systems with external disturbances in directed networks. In contrast to the existing constrained containment results that ignore disturbances, this work incorporates the disturbances, the position, and velocity constraints of followers simultaneously. A projection‐based control protocol is developed to pull all followers into a target area formed by some leaders, and meanwhile, a certain level of disturbance attenuation performance is satisfied. By utilizing the multiple model transformations, convexity analysis, and the Lyapunov approach, a sufficient condition is derived to realize the constrained containment with H ∞ H_∞ performance. Some simulation results are provided to demonstrate the disturbance‐rejection performance of the proposed control method.